Fetal sex determination in cattle by means of real-time b-mode ultrasonography - D. Ali Dinç; SaitŞendağ; H. Ahmet Çelik; İbrahim Aydın; Seyit Ümütlü; Faruk Aral (Eurasian Journal of Veterinary Sciences)
The objective of this study was to determined the fetal sex by ultrasound. Study was carried out in 115 pregnant heifers and cows between the days 55 to 120. The animals were groupped according to pregnancy days: group I (55 to 70); group II (71 to 90); group III (91 to 120) days of gestation. Ultrasound examinations were done Iransrectally using a real-time. B-mode, scanner equipped with a 5-7.5 MHz linear array transducer. Examinations were done only once in each animal and the examination time was limited to 15 minutes. Fetal sex was able to be obtained in 74 out of 115 animals. True and false diagnosis rate ol fetal sex in 74 cases was 78.4 % and 21.6 %, respectively. Accuracy rate in group I, II, III was 73.3 %, 82.4 % and 80 %. It was concluded that, ultrasound confirmation ol the fetal sex was 78.4%. Stage of the pregnancy and fetal position are influence in determination of fetal sex. Repeat or extented examination of lime was needed in the case of inappropriate fetal position. Determination of fetal sex was not acceptable in progressive pregnancy (91-120. pregnancy days).